A bird's eye view of two mimetic tropical butterflies: coloration matches predator's sensitivity. (25th November 2015) - Thurman, T. J.; Seymoure, B. M.
Abstract: Unprofitable prey with conspicuous warning signals are often mimicked by other species, which then gain protection from predators. How closely two mimetic species resemble one another depends upon the visual perception of the signal receiver. However, most studies of mimetic coloration have been conducted using only the human visual system, which differs greatly from that of most animals. To better understand mimicry, we should study mimetic visual signals through the eyes of the intended receiver. Here, we use avian visual models to test predictions of putative Batesian mimicry in two Amazonian butterflies, Mimoides pausanias and Heliconius sara . We calculated Just Noticeable Differences (JNDs) and tetrahedral color volumes for 11 different patches: iridescent blue, yellow bars, red spots and black background. Several color patches were not visually discriminable for both avian visual systems (UV/VIS and V/VIS), and visual discrimination (i.e. degree of mimicry) of color patches depended upon the avian visual system. These two butterfly species are more mimetic when viewed by their likely avian predators, which have V/VIS vision. Therefore, this mimetic assemblage may have evolved to be more spectrally accurate in the non‐UV wavelengths which their avian predators are able to see. However, while many color patches of the two species were modeled to be difficult to discriminate, most color patches were not perfect matches regardless of visual system, and several patches were very poor mimics. Through this study we demonstrate the importance of testing putative mimetic assemblages using known predator perceptual models and lay a foundation for behavioral studies to further test mimicry in H. sara and M. pausanius .